An experimental and thermodynamic study of sphalerite solubility in chloride-bearing fluids at 300–450 °C, 500 bar: implications for zinc transport in seafloor hydrothermal systems. (1st August 2022) - Xing, Yanlu; Brugger, Joël; Scheuermann, Peter; Tan, Chunyang; Ji, Shichao; Seyfried, William E.
Abstract: The solubility and speciation of zinc (Zn) in chloride-bearing aqueous fluids at high temperature and pressure are important for understanding Zn transport in natural hydrothermal systems and associated mineralizing processes. Here, we measured sphalerite solubility in NaCl-HCl-H2 O fluids using a fixed-volume titanium alloy hydrothermal reactor equipped with a newly designed gas-tight titanium piston sampler. This novel reactor-sampling system is capable of acquiring internally filtered fluids at high temperature and pressure. The experiments were conducted at 300–450 °C, 500 bar, in fluid with 0.5 m and 1 m NaCl, respectively. The measured sphalerite solubilities are consistent with predicted values using previous thermodynamic data at 300–400 °C, but diverge significantly above 400 °C. To resolve this discrepancy, we adjusted the solubility product of Zn minerals by modifying the heat capacity and Born coefficients that describe the Gibbs Free Energy of formation from the elements of the Zn 2+ aqua ion based on the new solubility data. The refined Helgeson-Kirkham-Flowers (HKF) equation of state (EoS) of Zn 2+ empirically reproduces the solubility data of Zn minerals from previous experimental studies well over the covered T-P range (25–600 °C, Psat to 2 kbar), but extends accurate predictions to conditions typical of deep sea hydrothermal systems, down to fluid densities of 0.35 g/cm 3 . Thermodynamic modelling using the revised EoS of Zn 2+ shows that higher temperatures, chlorinity and lower pH increase Zn solubility, and that Zn chloride complexes are the predominant species. The influence from salinity on Zn solubility is less significant in fluids with low pH. Applied to seafloor hydrothermal systems, our results suggest that in addition to temperature, pH and total dissolved chloride, fluid/rock ratio may be an important factor contributing to Zn concentrations in vent fluids at Mid Ocean Ridges.